The smell of spud-stress: a pilot study testing the viability of volatile organic compounds as markers of drought stress in potato (Solanum tuberosum) - Bell, Luke; Radha, Kala; Hill, Dominic (Frontiers in Plant Science, 2025)
IntroductionVolatile organic compounds (VOCs) are products of plant secondary metabolism with the potential for signalling early stress response. This pilot study investigated the potential of VOCs as markers for drought stress in potato. We hypothesised that differences in VOC emissions between cultivars may reflect genotypes with greater adaptive efficiency to drought stress.MethodsUsing thermal desorption collection and gas chromatography-mass spectrometry (GC-MS) techniques, we profiled the VOCs emitted by two potato cultivars, Maris Piper and Désirée, under well-watered and drought conditions, across a four-week period (n = 3 per cultivar, treatment, and time-point).ResultsWe identified 23 compounds, and tentatively identified another 49 compounds, including sesquiterpenes, alkanes, monoterpenes, and methylbenzenes. Statistical analysis revealed that seven compounds showed significant differences between cultivars and drought/well-watered treatments. Two farnesene isomers, a xylene isomer, 2,6-dimethyldecane, decahydronaphthalene, and 2-methyldecalin were identified as tentative markers of drought stress.DiscussionOur findings suggest that VOCs could be used for detection of drought stress in potato plants, contributing to improved irrigation management and the breeding of more drought-tolerant varieties. Further research is needed to validate these findings and explore the underlying mechanisms.